Three Consecutive Complete Hydatidiform Moles: A Rare and Challenging Pattern of Gestational Trophoblastic Disease - Tiffany Sudirman; Ummu Fatihah (International Medical Journal Corp. Ltd, 2026)
Introduction Recurrent hydatidiform mole is an uncommon gestational trophoblastic disease but is clinically important. Although a single molar pregnancy is generally well understood, consecutive recurrences remain rare and raise concerns regarding the underlying genetic predisposition, with implications for malignant progression and future reproductive outcomes. Case Illustration A 26-year-old woman presented with one month of vaginal bleeding with clots, lower abdominal pain, severe nausea, dizziness, and weakness. She had undergone three prior curettages (one miscarriage and two molar pregnancies). Inspection detected anemia, uterine enlargement, lower abdominal tenderness and visible tissue on the cervix. Ultrasound revealed a classic “snowstorm” pattern. Transfusion stabilized the patient, who had evacuation curretage. The patient was then referred to a tertiary care center for genetic identification and serial β-hCG surveillance. Discussion The risk of hydatidiform mole in subsequent pregnancies is known to increase in cases of previous hydatidiform mole. Recurrences occur in 1.3%-2% of women who have had hydatidiform mole and rise to 15% in women who have had two consecutive hydatidiform mole. It is more common in those of reproductive age (15-45 years) and in multiparous. Approximately 10% of all cases are prone to malignant transformation. Conclusion This case underscores the importance of considering recurrent cases of hydatidiform mole in woman with early pregnancy bleeding and prior molar history. Early ultrasonographic evaluation, histopathological confirmation, and prompt evacuation are essential to reduce morbidity. Careful postevacuation surveillance is critical to detect persistent trophoblastic disease and prevent malignant progression.